Participation, representativeness and democracy. Social movements in the construction of modern ethical and political systems in Latin America - Ríos Sangucho, Iván Patricio (2024)
Introduction. Today, social movements are considered to be key actors inthe development of politics worldwide. Their sudden appearance in this fieldis evidence of the emergence of new, alternative and necessary forms of social organization. Their intervention is marked by an aura of change and restitution of rights. In Latin America, these collectives arise from popular discontent and as a counterweight to political parties, evidencing a structural gap in the so-called representative democracies. Objective. In this context, the study seeks to analyze the importance of social movements in the construction of modern ethical-politicalsystems. Methodology. The research has a qualitative approach based on aliterature review from a conceptual and categorical basis. The concepts addressed include political systems, crisis of representation and plurality of identities, while the categories include democratization of power, loss of legitimacy of traditional political structures and recognition of diversity. Results. Social movements have contributed to reconfiguring power relations, promoting greater inclusion, justice and democratic sustainability, this as a consequence of a distrust in institutions and governance structures. Conclusions. It is concluded that social movements are a key element in the development of the so-called modern democracies in Latin America, since their participation generates spaces of representation and agency for socially and historically excluded groups in Latin America.